Black Bottom saints : a novel - Randall, Alice, 1959- (Amistad, an imprint of HarperCollinsPublishers, 2020)
In the black-owned-and-operated Kirkwood Hospital, Joseph 'Ziggy' Johnson reflects on his life. From the Great Depression through the post-World War II years, Ziggy had been the pulse of Detroit's famous Black Bottom. A celebrated gossip columnist for the city's African-American newspaper, the Michigan Chronicle, he was also the emcee of one of the hottest night clubs, where he rubbed elbows with the legendary black artists of the era. In his hospital bed, Ziggy curates his own list of Black Bottom's venerable '52 Saints,' local heroes whose unstoppable ambition, love of style and faith in community made this black Midwestern neighborhood the rival of New York City's Harlem.